2022
DOI: 10.3390/ma15248855
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pyrolysis Temperature and the Source Biomass on the Properties of Biochar Produced for the Agronomical Applications as the Soil Conditioner

Abstract: Biochar is a versatile carbon-rich organic material originating from pyrolyzed biomass residues that possess the potential to stabilize organic carbon in the soil, improve soil fertility and water retention, and enhance plant growth. For the utilization of biochar as a soil conditioner, the mutual interconnection of the physicochemical properties of biochar with the production conditions used during the pyrolysis (temperature, heating rate, residence time) and the role of the origin of used biomass seem to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
(78 reference statements)
0
20
0
Order By: Relevance
“…The ATR-FTIR spectra of particleboards made from rye straw contained several well-defined peaks that are characteristic of lignocellulosic materials. The presented spectra were interpreted based on the available literature data [ 49 , 50 , 51 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ATR-FTIR spectra of particleboards made from rye straw contained several well-defined peaks that are characteristic of lignocellulosic materials. The presented spectra were interpreted based on the available literature data [ 49 , 50 , 51 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, acidic surface functional groups decreased during carbonization [26,27,31]. Both mechanisms coincide, increasing biochar alkalinity as the pyrolysis temperature increases [42,54,63]. Furthermore, the pH of wooden biochar correlated with the pH of the feedstock, which could be used to predict the pH of biochar.…”
Section: The Vm MC Ash Fc and Ph Of Dbc Biochar Obtained From Various...mentioning
confidence: 92%
“…The effect of different pyrolysis temperatures on biochar properties has been widely studied for various feedstocks, including agricultural residues [50,51], wood chips and branches [52,53], and mixed wood wastes [54]. At a high temperature (500 °C), the carbon content in Neem wood biochar was 75.80% [55], that in pineapple leaf biochar was 60.79% [56], that in rice straw biochar was 61.98% [57], and that in corn stover biochar was 64.50% [51].…”
Section: Introductionmentioning
confidence: 99%
“…Biochar has shown potential for long-term sequestration of carbon [58]. Studies have shown that biochar's pyrolysis temperature significantly influences carbon sequestration, where higher pyrolysis temperatures produce biochar with a greater capacity for sequestering carbon than biochar produced with lower pyrolysis temperatures [57,[59][60][61]. Amending one hectare with biochar sequesters approximately 13 tons of CO 2 eq in the soil [62].…”
Section: Soil Total Organic Carbon (Toc)mentioning
confidence: 99%
“…Biochar captures and stores carbon in recalcitrant form, thereby reducing carbon emissions into the atmosphere [63]. Biochar use in agriculture is a feasible option for enhancing carbon sequestration and improving soil quality [59,64]. The recalcitrant nature of biochar is important for its application in carbon capture and sequestration, as highlighted by Zhang et al [59].…”
Section: Soil Total Organic Carbon (Toc)mentioning
confidence: 99%